Experimental colitis in IL‐10‐deficient mice ameliorates in the absence of PTPN22. (10th July 2019) - Jofra, T.; Galvani, G.; Cosorich, I.; De Giorgi, L.; Annoni, A.; Vecchione, A.; Sorini, C.; Falcone, M.; Fousteri, G.
Summary: Interleukin (IL)‐10 plays a key role in controlling intestinal inflammation. IL‐10 ‐deficient mice and patients with mutations in IL‐10 or its receptor, IL‐10R, show increased susceptibility to inflammatory bowel diseases (IBD). Protein tyrosine phosphatase, non‐receptor type 22 (PTPN22) controls immune cell activation and the equilibrium between regulatory and effector T cells, playing an important role in controlling immune homoeostasis of the gut. Here, we examined the role of PTPN22 in intestinal inflammation of IL‐10 ‐deficient ( IL‐10 –/– ) mice. We crossed IL‐10 –/– mice with PTPN22 –/– mice to generate PTPN22 –/– IL‐10 –/– double knock‐out mice and induced colitis with dextran sodium sulphate (DSS). In line with previous reports, DSS‐induced acute and chronic colitis was exacerbated in IL‐10 –/– mice compared to wild‐type (WT) controls. However, PTPN22 –/– IL‐10 –/– double knock‐out mice developed milder disease compared to IL‐10 –/– mice. IL‐17‐promoting innate cytokines and T helper type 17 (Th17) cells were markedly increased in PTPN22 –/– IL‐10 –/– mice, but did not provide a protctive function. CXCL1/KC was also increased in PTPN22 –/– IL‐10 –/– mice, but therapeutic injection of CXCL1/KC in IL‐10 –/– mice did not ameliorate colitis. These results show that PTPN22 promotes intestinal inflammation in IL‐10 ‐deficient mice, suggesting that therapeutic targeting of PTPN22 might be beneficial in patients with IBD and mutations in IL‐10 and IL‐10R . Abstract : PTPN22 promotes acute DSS‐induced experimental colitis in IL‐10‐deficient mice. (a) Weight was measured in DSS‐treated mice daily (WT, n = 15; PTPN22 ‐/‐, n = 15; IL‐10 ‐/‐, n = 17 and PTPN22 ‐/‐ IL‐10 ‐/‐, n = 13). Graph shows daily weight change (in percentage) as compared to the initial weight. (b) Percentage of weight change from initial weight of DSS‐treated mice of (a) analyzed at day 8. (c) Colon length among DSS‐treated mice at day 8 expressed in cm. (d‐e) Colitis score and representative H&E colon sections from DSS‐treated mice of the indicated genotypes ( n = 3/group). (f) Spleen weight in grams analyzed in DSStreated mice at day 8.